A modified practical homodyne detector model for continuous-variable quantum key distribution: detailed security analysis and improvement by the phase-sensitive amplifier. (17th December 2020) - Huang, Yundi; Zhang, Yichen; Xu, Bingjie; Huang, Luyu; Yu, Song
Abstract: The practical homodyne detector model of continuous-variable quantum key distribution models the inherent imperfections of the practical homodyne detector, namely the limited detection efficiency and the electronic noise, into trusted loss. However, the conventional practical homodyne detector model is valid only when both the imperfections of the practical homodyne detector are calibrated. In this paper, we show a modified practical homodyne detector model that can model the imperfections separately. The phase-sensitive amplifier (PSA) is further applied to compensate the imperfections of the practical homodyne detector. The feasibility of the modified practical homodyne detector model with the PSA is proved and the security analysis is provided in detail. Simulation results reveal that the PSA can be used to improve the performance of the modified practical homodyne detector model, and when the gain is infinitely high, the limited detection efficiency can be fully compensated.